2012
DOI: 10.1186/1556-276x-7-330
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of platinum and silver into chemically modified microporous silicon electrodes

Abstract: Electrodeposition of platinum and silver into hydrophobic and hydrophilic microporous silicon layers was investigated using chemically modified microporous silicon electrodes. Hydrophobic microporous silicon enhanced the electrodeposition of platinum in the porous layer. Meanwhile, hydrophilic one showed that platinum was hardly deposited within the porous layer, and a film of platinum on the top of the porous layer was observed. On the other hand, the electrodeposition of silver showed similar deposition beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…It has been shown that Pt is deposited within the pores in using hydrophobic structures, whereas it is only deposited on the top surface in the case of hydrophilic porous silicon. Ag deposits for both chemically modified structures equally [45]. In Figure 1 Pt deposited within a porous silicon layer is depicted.…”
Section: Fabrication and Metal Filling Of Microporous Siliconmentioning
confidence: 99%
“…It has been shown that Pt is deposited within the pores in using hydrophobic structures, whereas it is only deposited on the top surface in the case of hydrophilic porous silicon. Ag deposits for both chemically modified structures equally [45]. In Figure 1 Pt deposited within a porous silicon layer is depicted.…”
Section: Fabrication and Metal Filling Of Microporous Siliconmentioning
confidence: 99%
“…However, both studies did not show the morphologies of the filled pores. Koda et al (2012) studied electrodeposition of platinum and silver into chemically modified microporous silicon and established that when the pore diameter of PSi is extremely small, platinum deposition is strongly affected by the hydration property of the pore wall. On the other hand, silver deposition is not affected by the property.…”
Section: Electrochemical Processesmentioning
confidence: 99%
“…On the other hand, silver deposition is not affected by the property. According to Koda et al (2012), these results could be explained by the difference in overpotential between the deposition on the metal surface and that on the silicon surface, and by the difference in intrinsic displacement deposition rate of metal. It was also established that when metal electrodeposition is carried out in microporous silicon, the effect of the overpotential and the displacement deposition rate should be considered together with the hydration property of the metal ions.…”
Section: Electrochemical Processesmentioning
confidence: 99%
“…By varying the electrolyte composition, the values of the cathodic potential or current density, and the methods of current supply (stationary, cyclic, and pulsed), it is possible to obtain MNPs of various shapes and sizes on the silicon surface. Most of the studies on electrochemical production of MNPs/Si surface systems have been performed in aqueous solutions (see Table 1) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. However, the water factor as a medium does not always provide the ability to control the geometry of MNPs at the main stages of their formation: cathodic reduction (1), nucleation, i.e., formation of metal nanoclusters (MNCs) (2), and nanoparticles (3).…”
Section: Introductionmentioning
confidence: 99%